Cuantificación de bacterias celulolíticas anaerobias provenientes del rumen de ganado bovino : comparación de tres técnicas (2011)
ABSTRACT: Rumen microorganisms are responsible for digestion of plants material consumed by ruminants. Cellulolytic bacteria have the ability to degrade structural carbohydrates, so the abundance and enzymatic activity of these is essential for developing strategies to manipulate the rumen fermentation. Objective Compare the methods for quantification of bacterial growth: most probable number, viable cell count and Roll-tube plate for enumeration of rumen bacteria. Materials and methods Comparative experimental study. We evaluated three methods for quantification of bacterial growth: most probable number, viable cell count and Roll-tube plate with respect to the density and diversity of ruminal cellulolytic bacteria in rumen fluid samples collected from two cannulated Holstein females to rumen. Results High and positive correlation was observed with statistical significance (0.826; p=0.000) between the quantification of viable cells by the Roll Tube method and the plaque viable cells quantification method. Another correlation, this time negative, moderated and weak, was observed between the quantification of viable cells obtained by the “most probable number” method with the Roll Tube method and the plaque method too. (-0.514; p=0.237;-0.374; p=0.147 respectively). The results from the determination coefficient corroborate this information. On the one hand, the “most probable number” method detected low diversity, on the other hand the other methods (Roll Tube and plaque), demonstrated consistency with regard to density and bacteria diversity. Conclusions The data suggest that the technique of counting viable cells in plaque may be most appropriate to quantify ruminal cellulolytic bacteria.